Senegal : Report on Observance of Standards and Codes-Data Module. (IMF Staff Country Reports; Country Report, 2002)
This Report on the Observance of Standards and Codes data module provides a review of Senegal's data dissemination practices against the IMF's General Data Dissemination System, complemented by an in-depth assessment of the quality of the national accounts, consumer price index, government finance, monetary balance of payments, and income poverty statistics. The assessment reveals that Senegal generally follows the recommendations of this system for the coverage, periodicity, and timeliness of all data categories. Overall, the institutional environment of the data-producing agencies supports statistical quality.